Effect of integrated nitrogen management on growth and yield of okra (Abelmoschus esculentus under teak (Tectona grandis) based silvi-horticulture system in south Gujarat - Mevada R J; Tandel, Minalkumar Bhagvanbhai; Patel N K (Indian Journal of Agroforestry, 2023)
South Gujarat region is suitable for growing okra and conventional teak plantation. Therefore, present investigation was carried out to study the effect of integrated nitrogen management (INM) on growth and yield of okra under teak based silvi-horticulture system in South Gujarat during year 2019 and 2020 in Summer season. An experiment was framed in randomized block design with eleven different treatments comprised of combinations of vermicompost, neem cake and chemical fertilizers in various proportions (i.e. 25, 50, 75 and 100 per cent) of Recommended Dose of Nitrogen (RDN). Okra cv. GAO-5 was sown in the inter spaces of 23 year old teak plantation and applied different integrated nitrogen management treatments in the form of organic and inorganic fertilizers to okra under teak and in open condition. The result showed that majority of growth, reproductive and yield parameters of okra were recorded maximum with application of 75% RDN through neem coated urea + 25% RDN through vermicompost in open condition and also same treatment application showed the good performance of okra under teak based silvi-horticulture system. Whereas, minimum growth, reproductive and yield parameters were recorded with application of 100% RDN through neem cake under teak based silvi-horticulture system. But, the teak based silvi-horticulture system ensures additional return and more sustainable than sole cropping.